Ethical Turn of Humanitarian Normativism: The Right to be Mourned (2022)
Because of our intense desire to deny our own death when confronted with the death of others, our spiritual deflation presents an ethical and political opportunity, rather than an insurmountable obstacle, to think about and build other discourses and normative practices in the face of the destructiveness that we are capable of and are irremediably exposed to anyway. Undoubtedly, the norms of apprehension and recognition of what is human depend, above all, on our affective dispositions when confronting the death of others, whose losses we judge, differentially, as meritorious or unworthy of being mourned, according to the value or lack of value we ascribe to their lives; hence, the importance of the right to be mourned as an ethical and political condition for the humanization of all. This article, based on Aeschylus, Sigmund Freud, and Judith Butler, comprises three sections: (1) the question of human destructiveness; (2) killable lives that are unworthy of mourning; and (3) the affective power of mourning.